1976
DOI: 10.1112/jlms/s2-13.3.387
|View full text |Cite
|
Sign up to set email alerts
|

Decomposition of Precompact Operators in Ordered Locally Convex Spaces

Abstract: The concept of a-directedness in a partially ordered Banach space X was first introduced by Asimow [1], Some studies of this property have since been made by Rogalski [7] and Wickstead [8]. In [8], it is shown that a-directedness is equivalent to the order-boundedness of compact subsets of X and is relevant to the positively generating property of the spaces of compact operators into X. In this paper, we generalize the result of Rogalski and Wickstead to the setting of metrizable locally convex spaces.From no… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

1981
1981
2015
2015

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 2 publications
(2 reference statements)
0
4
0
Order By: Relevance
“…In [3], it was shown that, for Banach spaces, (i) of Theorem 2 implies a formally much stronger version of directedness property: each compact subset of the open unit ball U in E is majorized by an element in U. Again some simple examples show that the implication may not hold for non-complete spaces (e.g.…”
Section: Theorem 1 If (Ea) Is An Approximate Order-unit For ~H Thenmentioning
confidence: 96%
“…In [3], it was shown that, for Banach spaces, (i) of Theorem 2 implies a formally much stronger version of directedness property: each compact subset of the open unit ball U in E is majorized by an element in U. Again some simple examples show that the implication may not hold for non-complete spaces (e.g.…”
Section: Theorem 1 If (Ea) Is An Approximate Order-unit For ~H Thenmentioning
confidence: 96%
“…It turns out that if null sequences in a Banach algebra factor then maximal right ideals are closed-see [ In order to prove that null sequences in S factor we cannot follow the Banach-algebra proof of Varopoulos, who proved in [24] that if a Banach algebra admits a bounded approximate identity then null sequences in this algebra factor. Instead we will rely on [1] and [9]. Our proof will be divided into several steps.…”
Section: Closedness Of Maximal One-sided Idealsmentioning
confidence: 99%
“…The next step is to show that S sa is quasi-directed. An ordered locally convex space is (see [9]) quasi-directed if for any neighbourhood U of zero there is another neighbourhood V of zero such that every finite subset of V is majorized by some element of U . We will now prove that the ordered self-adjoint part of the non-commutative Schwartz space is quasi-directed.…”
Section: Proposition 3 S Sa Ismentioning
confidence: 99%
See 1 more Smart Citation